‘Why Don't We Get Counselling?’: Comparing NICE Guidelines for Morphological and Genetic Cancer Risk Diagnoses - Elspeth Davies (Cancer Medicine)
ABSTRACT Background In the UK's National Health Service (NHS), there is specific psychosocial care offered to people with genetic cancer risk conditions but not morphological cancer risk conditions. As researchers develop new ways to diagnose morphological risk conditions, including precancers and in situ cancers, it is important to consider the psychosocial care that those diagnosed might require. Objectives This study compares the National Institute for Health and Care Excellence's guidelines for BRCA1/2, which are genetic risk conditions, and Barrett's oesophagus (BO), a morphological risk condition. It then theorises reasons for the similarities and differences made visible by this comparative work. Methods The author completed an in‐depth analysis of two sets of NICE guidelines, before carrying out a review of historical and social scientific literature on cancer risk to offer potential explanations for the disparities identified. Results The ‘right not to know’ is protected in the case of BRCA1/2 diagnoses, but not BO. Additionally, specialist counselling is required for people receiving diagnoses of genetic risk but not offered for those diagnosed with morphological risk conditions. The paper offers four possible reasons for these disparities, concluding that they appear to be in large part due to historic genetic exceptionalism, rather than differences in patients' needs. Conclusion There may be a need to consider offering further psychosocial care to people with morphological risk conditions like BO. Lessons might be learnt from the field of genetic counselling.